Ethical Reasoning: The Impact Of Ethical Dilemma, Egoism And Belief In Just World - Ahmad, Noor Hazlina; A. Ansari, Mahfooz; Aafaqi, Rehana (Asian Academy of Management (AAM), 2005)
Following a 3 [dilemma: coercion and control (CC); conflict of interest (CI); personal integrity (PI)] × 2 (egoism: self; organization) × 2 (belief in just world (BJW): strong; weak) between-subjects factorial design, we hypothesized the main effects of ethical dilemma, egoism, and BJW, and their interaction on ethical reasoning. The first two factors were manipulated by means of six vignettes and the last factor was a subject variable. Experimental participants were 384 managers representing 14 manufacturing organizations. Overall, utilitarian reasoning appeared to be a frequently used type of reasoning in relation to personal integrity dilemma involving self-interest, whereas principled reasoning appeared to be a frequently used reasoning in relation to personal integrity dilemma involving organizational-interest. BJW interacted strongly with the two manipulated factors in predicting ethical reasoning. Implications of the study are discussed, potential caveats are specified and recommendations for future research are provided.